Pengukuran Beban Kerja Mental Job Driver Dan Swamper Team Fuel Menggunakan NASA-TLX - Muhammad Qurthuby (Jurnal Surya Teknika, 2021)
Giving excessive workloads causes work stress both physically and psychologically and emotional reactions. The excess workload experienced by drivers and swampers at PT XYZ results in reduced attention at work, decreased work motivation, and decreased skill levels, thus affecting drivers and swampers productivity and the chance of a work accident is very high. This study aims to measure the Mental Workload of Job Driver and Swampers Fuel Tank Using the NASA-TLX Method. The NASA-TLX score obtained 93.8, driver 2 get 83.7, driver 3 91.3, swamper 1 91, swamper 2 89.5, and swamper 3 94.7. Elements of mental workload that are very influential are Mental Demand with a percentage of 22%, Effort 20%, Physical Demand 18%, Own Performance 15%, Frustation Level 15% and Temporal Demand 12%.